TRADISI MAUDU LOMPOAA DI DESA CIKOANG KECAMATAN LAIKANG KABUPATEN TAKALAR : ANALISIS FILSAFAT NILAI MAX SCHELER - Anisa, Nur; Nurbaety, Andy; Veranita Indah, Astrid (Sulesana, 2025)
This research was motivated by the author's curiosity about the Maudu Lompoa tradition in Cikoang Village, Laikang District, Takalar Regency, which is a unique form of religious celebration with a blend of cultural and spiritual values ​​and Sufism teachings. Using a qualitative field approach, data was obtained through direct observation techniques, interviews with informants, and documentation of activities. The results of the study indicate that this tradition has strong religious values ​​and reflects the teachings of Sufism: sharia, tarekat, hakikat, and ma'rifat. Based on Max Scheler's philosophy of values, this tradition reflects the entire hierarchy of values, starting from aspects of pleasure, life values, spiritual values, to the peak of holiness. The Maudu Lompoa tradition not only strengthens religious and social values, but also has the potential to be developed as a religious cultural tourism destination that has educational and economic value.